Retrofitting Strategies for Earthquake Safe Existing Reinforced Concrete Building: An Overview: Methods and Technologies for Retrofitting Existing Structures (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Retrofitting of existing structures offers noteworthy open doors for diminishing worldwide vitality utilization and ozone depleting substance emissions. This paper gives a methodical way to deal with legitimate determination and distinguishing proof of the best retrofit alternatives for existing structures. An overview of the innovative work and in addition utilization of the retrofit advances in existing structures is additionally given.